PMO-229 MicroRNA expression profiling in stricturing Crohn's disease identifies miR-34a as a functionally relevant influence on disease phenotype. (28th May 2012) - Nijhuis, A; Biancheri, P; Lai, C; Ghosh, A; Boitsova, T; Chan, C; MacDonald, T; Lindsay, J; Silver, A
Abstract : Introduction: Intestinal fibrosis is a frequent complication in Crohn's disease (CD), with subsequent stricture development that may require surgical intervention. MicroRNAs (miRNAs) are a novel class of post-transcriptional gene regulators implicated in cardiac, hepatic and pulmonary fibrosis. MiRNAs play a key role as modulators of the potent pro-fibrotic cytokine transforming growth factor (TGF)-β, which is up-regulated in CD intestinal strictures. Here, we aimed to identify and investigate the functional characteristics of miRNAs with differential expression between strictured and non-strictured CD. Methods: Intestinal surgical specimens were collected from 17 patients with fibrostenosing CD, and total RNA was extracted from uninflamed ileal mucosa. MiRNA expression profiling was performed using Illumina v2.0 microRNA array comparing matched strictured to non-strictured areas from the same patient within each experimental group. Subsequent validation of differentially expressed miRNAs was performed using qRT-PCR. Primary mucosal fibroblast cultures were derived from strictured CD and healthy control tissue. Overexpression of miRNAs was induced by transfection with Dharmafect agent under optimised conditions and changes in mRNA expression were detected by RT-qPCR and protein expression by IHC and Western Blotting. Results: We detected 11 miRNAs significantly up-regulated and 10 miRNAs significantly down-regulated (all p<0.02) between the strictured and non-strictured ileum. Validation experiments confirmed the changes of miR-34a in an independent set of 8 matched strictured vs non-strictured tissues. MiR-34a has been identified as a direct target of P53 which is involved in murine kidney fibrosis. When overexpressed in primary fibroblast cell lines, miR-34a increases expression of COL1A2 and COL3A1 mRNA in strictured CD cell line. However, upregulation of P53 mRNA or protein was not detected in 6 matched paired tissues, indicating a P53-independent mechanism by which miR-34a exerts its pro-fibrotic effects. Conclusion: This study confirms that differences in miRNA expression profiles between CD strictured and non-strictured areas can be detected. Upregulation of collagen mRNA shows that miR-34a might play a functional role in modulating fibrosis in CD, however further studies to investigate the impact of increased collagen protein are required. Manipulation of miRNA profiles may be a novel therapeutic strategy against fibrosis in Crohn's disease. Competing interests: None declared.